Peran Pondok Pesantren dalam Mencegah Paham Radikalisme di Kabupaten Rejang Lebong - Syaiful Bahri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objective of the study was to analyze the role of islamic boarding school in preventing radicalism in Rejang Lebong regency. The study used qualitative approach with descriptive method. The data collection was done though interview, documentation and observation. The result showed that in playing the role, islamic boarding school recently became the target of people's distrust: this was the place of radicalism and terrorism. According to the analysis, there was no school found as the place of radicalism and terrorism. Some schools even actively prevent radicalism and terrorism effectively. In conclusion, the role of islamic boarding schools in Rejang Lebong to prevent radicalism and terrorism through the tight control was effective. Keywords: Islamic Boarding School, Radicalism, Terrorism